2021
DOI: 10.1016/j.ejrad.2021.109996
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic differentiation of breast cancer molecular subtypes using pre-operative breast imaging – A systematic review and meta-analysis

Abstract: Breast cancer has four distinct molecular subtypes which are discriminated using gene expression profiling following biopsy. Radiogenomics is an emerging field which utilises diagnostic imaging to reveal genomic properties of disease. We aimed to perform a systematic review of the current literature to evaluate the value radiomics in differentiating breast cancers into their molecular subtypes using diagnostic imaging. Methods: A systematic review was performed as per PRISMA guidelines. Studies assessing radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 61 publications
1
18
0
1
Order By: Relevance
“…The linear discriminant analysis method was also able to differentiate Luminal B with 75% AUC by using only one principial component via the quantile method. This was in line with the recent literature, which states that radiomic assessment of breast imaging can provide an option in determining breast cancer molecular subtypes [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The linear discriminant analysis method was also able to differentiate Luminal B with 75% AUC by using only one principial component via the quantile method. This was in line with the recent literature, which states that radiomic assessment of breast imaging can provide an option in determining breast cancer molecular subtypes [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we focused our attention on the luminal A and luminal B subtypes of breast cancer. Several studies have also explored the use of radiomics to investigate Luminal A and B breast cancer patients [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…DCE-MRI features were found to be associated with the deregulation or genetic alterations of some important pathways such as the mTOR pathway and oncogenic signaling pathways ( 22 , 23 ). Some works also attempted to establish prediction models for clinical biomarkers (such as ER and PR) as well as immunohistochemistry (IHC) subtypes of BC based on quantitative imaging features with a machine learning or deep learning approach ( 25 33 ). A study combined the MRI features from both peritumoral and intratumoral regions to predict the HER2-enriched molecular subtype and achieve an area under the curve (AUC) of 0.89 ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study combined the MRI features from both peritumoral and intratumoral regions to predict the HER2-enriched molecular subtype and achieve an area under the curve (AUC) of 0.89 ( 31 ). In a recent large meta-analysis, the IHC subtypes of BC were predicted non-invasively by the radiomics analysis based on MRI features ( 33 ). In addition, uncovering the ability of imaging features to assess the treatment response and predict clinical outcomes in BC is a valuable research aspect.…”
Section: Introductionmentioning
confidence: 99%
“…A newly published meta-analysis has shown that there are currently more than 40 studies concerning the radiomics assessment of molecular subtypes of breast cancer, most of which are based on mammography, ultrasound, and MRI ( 21 ). Huang et al.…”
Section: Discussionmentioning
confidence: 99%